1980
DOI: 10.1207/s15328023top0703_3
|View full text |Cite
|
Sign up to set email alerts
|

Instructionally-Based Training in Self-Control: Behavior-Specific and Generalized Outcomes Resulting from Student-Implemented Self-Modification Projects

Abstract: Significant pre-post changes in outcome measures, differences between successful and unsuccessful students on expectations, and other factors are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…The present study also demonstrated that SM course participation positively influenced students’ cognition, consistent with previous studies (Hamilton, 1980; Menges & Dobroski, 1977). For example, students in the high-intensity SM course reported increased expectancy of success and a greater sense of internal locus of control at the completion of the semester.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study also demonstrated that SM course participation positively influenced students’ cognition, consistent with previous studies (Hamilton, 1980; Menges & Dobroski, 1977). For example, students in the high-intensity SM course reported increased expectancy of success and a greater sense of internal locus of control at the completion of the semester.…”
Section: Discussionsupporting
confidence: 93%
“…Findings address several areas of interest. First, the acquisition and application of SM principles and skills through a college-level SM course were found to be effective in modifying a target behavior, which is consistent with previous findings (Dodd, 1986;Hamilton, 1980;Menges & Dobroski, 1977;Payne & Woudenberg, 1978;Rakos & Grodek, 1984). However, the major difference between the present results with that of previous findings is that the level of successful behavioral change was dependent on SM course intensity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations